Toxic Haemorrhagic Colitis: A Rare Presentation of Eosinophilic Colitis - Shen-Ann Eugene Yeo; Yon Kuei Lim; Kiat Hon Tony Lim; Choong-Leong Tang (Case Reports in Gastrointestinal Medicine)
Eosinophilic colitis is a rare condition that usually presents with non specific abdominal symptoms. Very uncommonly it presents with an acute surgical emergency such as peritonitis or haemorrhage. We present a rare presentation of eosinophilic colitis with toxic hemorrhagic colitis and ischaemic bowel requiring laparotomy and bowel resection.